BEBERAPA ASPEK DIMENSI NILAI AKSIOLOGIS MAX SCHELER DAN RELEVANSINYA PADA PRAXIS INTER-FAITH - Roma Ulinnuha (Religi: Jurnal Studi Agama-agama, 2016)
Based on what accentuated by Max Scheler on axiological dimension, thisarticle seeks to explore what aspects discussed in the axiological values and therelevance of the values on interfaith initiatives. The ever-present issues of conflict,radicalization and religiously-motivated violence has led the idea on how toapproach some ways toward the alternative solution. The queries are what isaxiological dimension of values in Scheler’s perspective? and what is the relevanceof the values on interfaith realm in religious studies perspective? The study showsthat the axiological dimension consisting of the values that needed to be foundobjectively as the ethical basis for human interaction in everyday life. In Scheler’sview, human without values is absurd; one needs moral values in order to live ameaningful life. The essence of values is present with or without human’s practice.The relevance of the value is profound in interfaith realm since it forms humanidentity and determines peaceful coexistence among people of different faiths.